EKSEKUSI JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI (MK) NOMOR 18/PUU-XVII/2019 PADA LEMBAGA PEMBIAYAAN KONSUMEN - Sundaru Guntur W (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to identify and understand the implementation of the consumer financing agreement and the resolution of problems that arise in the event of a default by the debtor in the implementation of the consumer financing agreement. This research is specific to the handling of late payments or even bad loans, which then the object of the agreement is executed / withdrawn by the debtor associated with the Decision of the Constitutional Court (MK) Number 18/PUU-XVII/2019 against consumer financing institutions. This study uses an empirical juridical approach. , using primary data and secondary data which is then analyzed using qualitative analysis techniques.